If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -9h + -15 = 7h + 22 + -8h Reorder the terms: 13 + -15 + -9h = 7h + 22 + -8h Combine like terms: 13 + -15 = -2 -2 + -9h = 7h + 22 + -8h Reorder the terms: -2 + -9h = 22 + 7h + -8h Combine like terms: 7h + -8h = -1h -2 + -9h = 22 + -1h Solving -2 + -9h = 22 + -1h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add 'h' to each side of the equation. -2 + -9h + h = 22 + -1h + h Combine like terms: -9h + h = -8h -2 + -8h = 22 + -1h + h Combine like terms: -1h + h = 0 -2 + -8h = 22 + 0 -2 + -8h = 22 Add '2' to each side of the equation. -2 + 2 + -8h = 22 + 2 Combine like terms: -2 + 2 = 0 0 + -8h = 22 + 2 -8h = 22 + 2 Combine like terms: 22 + 2 = 24 -8h = 24 Divide each side by '-8'. h = -3 Simplifying h = -3
| 2(4n-11)+8=5n+4 | | 82=12m | | 3*s=330 | | 3(t-4)=5(t+1)-1 | | 2x=4(x+3) | | -12x=-120 | | 45x^2+20x=45x+20 | | -16=-25-x | | 6p+p=7p | | -5/8w+2/5=-7/8w+1/8 | | 5x^2+x-328=0 | | -7=-10+x | | X^2+11x+35=5 | | 8P^4*3p= | | 25x-5+10x= | | 2x^4-4x^3-3=0 | | 3-2/2+6=z+8 | | X^2+42X-43=0 | | 7-3x=x-4(2+6) | | b+3=33-b | | 3-9=4x+4 | | x=250+0.8(x-(325+0.25x))+650-80i+560 | | 1x^2-30x=0 | | 6x^2-5x=x | | 4x-12=24+8x | | 11x+12y=150 | | (x^2+7x-48)/(x+9) | | 6x-3(x-4)=2(x+7)+x | | p^2-13p+36=0 | | 4x+16=-12 | | 10-2x=9-5x | | 4(3x-5)=4x+4 |